2017
DOI: 10.1111/1460-6984.12353
|View full text |Cite
|
Sign up to set email alerts
|

Spoken sentence production in college students with dyslexia: working memory and vocabulary effects

Abstract: College students with dyslexia were significantly less facile and flexible on this spoken sentence-production task than typical readers, which is consistent with previous studies of school-age children with dyslexia. Group differences in performance were traced primarily to limited working memory, and were somewhat mitigated by strong vocabulary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 66 publications
(206 reference statements)
0
9
0
Order By: Relevance
“…These mutations have been linked to short-and long-term learning and memory impairments in mice models (Chen et al 2010) and individuals with RTS show working memory span deficits relative to their overall mental age (Waite et al 2016). Working memory span is associated with vocabulary acquisition (Newbury et al 2015;Ellis and Sinclair 1996;Gathercole and Baddeley 1993;Gupta and MacWhinney 1997) and speech and sentence production (Wiseheart and Altmann 2018;Adams 1996;Acheson and MacDonald 2009). These skills are likely to be important for building more complex social communication skills and social responses and may contribute to the lack of development of these components of sociability in those with RTS.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations have been linked to short-and long-term learning and memory impairments in mice models (Chen et al 2010) and individuals with RTS show working memory span deficits relative to their overall mental age (Waite et al 2016). Working memory span is associated with vocabulary acquisition (Newbury et al 2015;Ellis and Sinclair 1996;Gathercole and Baddeley 1993;Gupta and MacWhinney 1997) and speech and sentence production (Wiseheart and Altmann 2018;Adams 1996;Acheson and MacDonald 2009). These skills are likely to be important for building more complex social communication skills and social responses and may contribute to the lack of development of these components of sociability in those with RTS.…”
Section: Discussionmentioning
confidence: 99%
“…Impairments in structural language skills have however been reported in some previous studies of adults with dyslexia. A recent study by Wiseheart and Altmann (2018) using a spoken sentence generation task found that dyslexic college students were slower to respond and produced sentences that were less fluent, grammatical and complete. These demonstrations of impairments in structural language skills in high achieving dyslexic students are striking.…”
Section: Discussionmentioning
confidence: 99%
“…A seminal meta‐analysis by Swanson and Hsieh (2009) found that adults with reading disabilities demonstrated a range of deficits on standardized measures that extended beyond a phonological core deficit, for example with additional impairments on naming speed and verbal memory. A recent study by Wiseheart and Altmann (2018) reported that high achieving dyslexic university students were impaired on a spoken sentence generation task relative to controls, being slower to respond and constructing sentences that were less precise and less fluent. Other studies have reported a sparing of vocabulary skills (e.g., Hatcher, Snowling, & Griffiths, 2002), with one study even reporting superior performance on a measure of vocabulary depth in French speaking dyslexic students compared to controls (Cavalli et al, 2016).…”
Section: Language Abilities In Adults With Developmental Disordersmentioning
confidence: 99%
“…Moreover, fMRI studies demonstrated thatregions of the parietal lobes, which are importantbrain structures involved in learning disabilities,have consistently been involved in motor skilllearning and fronto-parietal interaction have beenemphasized, also as reported by Cavalli E et al 25 ,parietal, supplementary motor area andcerebellum are involved in hand and finger movernents 26 . Furthermore, cerebellar activitieshave observed in several studies and theactivation pattern in non-motor skill learning issimilar to that of motor skill learning 27 . Second,PMS utilize neural connections that have beenprototypical for academic skills.…”
Section: Discussion:-mentioning
confidence: 84%